External Validity of Contingent Valuation: Comparing Hypothetical and Actual Payments. (9th October 2016) - Ryan, Mandy; Mentzakis, Emmanouil; Jareinpituk, Suthi; Cairns, John
Abstract: Whilst contingent valuation is increasingly used in economics to value benefits, questions remain concerning its external validity that is do hypothetical responses match actual responses? We present results from the first within sample field test. Whilst Hypothetical No is always an Actual No, Hypothetical Yes exceed Actual Yes responses. A constant rate of response reversals across bids/prices could suggest theoretically consistent option value responses. Certainty calibrations (verbal and numerical response scales) minimise hypothetical–actual discrepancies offering a useful solution. Helping respondents resolve uncertainty may reduce the discrepancy between hypothetical and actual payments and thus lead to more accurate policy recommendations. Copyright © 2016 John Wiley & Sons, Ltd.